Design of New Evaluation Model Based on Discrepancy Daiwi Asuri Sampad - Dewa Gede Hendra Divayana; I Putu Wisna Ariawan; Agus Adiarta (Emerging Science Journal, 2022)
The effectiveness of flipped learning can be realized if the dominant aspects that become positive and negative inequalities are known from the beginning. Positive inequality is used to indicate aspects that support the successful flipped learning implementation. Negative inequality is used to indicate aspects that need attention for improvement in a better direction. The reality is very difficult to determine the aspects that are included in the positive and negative inequalities. Therefore, an innovation of the IT education evaluation model is needed to be able to solve those problems. The DIVAYANA model that is modified with the Discrepancy model and integrated with the Daiwi Sampad and Asuri Sampad concepts can be used as an innovation in the field of IT education evaluation. The main objective of this research was to show the design quality of the new evaluation model integrated with Balinese local wisdom. It is called the DIVAYANA model based on the Discrepancy Daiwi Asuri Sampad which can be used to evaluate the effectiveness of flipped learning implementation at IT vocational schools. This research was carried out by following the stages of the Borg and Gall development model. This research only focused on five stages from a total of ten development stages. Those stages included: 1) research and field data collection, 2) planning, 3) design development, 4) initial trials, and 5) revision of initial trials. The subjects involved in collecting field data were six people. The subjects involved in planning and designing of evaluation model were three people. The subjects involved in the initial trials were 44 people. Subjects involved in the revision of initial trial results were three people. Questionnaires were used to collect field data and conduct preliminary trials. The results of data collection from the initial trial results were analyzed using quantitative descriptive analysis techniques by percentage descriptive calculations. The results showed that the quality level of the DIVAYANA model design based on the Discrepancy Daiwi Asuri Sampadwas 88.25%. So that the design was included in the good category and can be used to determine the dominant aspects that become the positive and negative inequalities in flipped learning implementation. The contribution of this research to the field of education is to show the existence of a new evaluation model in the IT education field which can be used to determine the dominant aspects that become positive and negative inequalities in supporting the successful flipped learning implementation at IT vocational schools. Doi: 10.28991/ESJ-2022-06-01-013 Full Text: PDF